Developmental status of NICU admited low birth weight preterm neonates at 6 and 12 months of age using Ages and Stages Questionaire - FALLAH, Razieh; ISLAMI, Zia; MOSAVIAN, Toktam (Iranian Journal of Child Neurology, 2011)
Objective Low birth weight (birth weight<2500g) can be one of the serious problems in children. The purpose of this study was to evaluate the developmental status of LBW preterm neonates admited at neonatal intensive care unit (NICU) at the corrected ages of six and 12 months via the Persian version of Ages and Stages Questionnaires (ASQ). Materials & Methods In a follow up study, fifty LBW preterm neonates admitted to Shahid Sadoughi Hospital NICU in 2008 were evaluated for developmental status at 6 and 12 months of age using ASQ. Results Twenty four boys and 26 girls with a mean gestational age of 31.3 ± 2.7 weeks and a mean birth weight of 1480.3 ± 422.8 grams were evaluated. Developmental delay in gross motor and personal social skills domains were the most prevalent abnormal developmental status at 6 and 12 months of age. Mean score in gross motor skills, personal social skills and porblem solving domains at 12 months of age were significantly higher in neonates with birth weight 1500 grams. Mean score in fine motor skills, communication and problem solving domains at 12 months of age were significantly higher in neonates who were exclusively breast fed. Conclusion LBW and preterm infants admitted to the NICU showed degrees of developmental delay at the ages of 6 and 12 months, especially in the gross motor and personal-social developmental domains on the ASQ. So, evaluation and monitoring of development status of LBW should be emphasized for early and timely diagnosis, investigation, and management.